The Dust Planet Clarified Modelling Martian MY29 Atmospheric Data using the Dynamic-Atmosphere Energy-Transport (DAET) Climate Model (Global Journal of Science Frontier Research, 2023)
The Dynamic Atmosphere Energy Transport DAET climate model a mathematical model previously applied to a study of Earth s climate has been adapted to study the climatic features in the low-pressure dust-prone atmosphere of the planet Mars Using satellite data observed for Martian Year 29 MY29 temperature profiles are presented here that confirm the studies of prior authors of the existence on Mars of a tropical solar-energy driven zone of daytime atmospheric warming that both diurnally lifts the tropopause and follows the annual latitudinal cycle of the solar zenith This tropical limb of ascending convection is dynamically linked to polar zones of descending air the seasonal focus of which is concentrated over each respective hemisphere s polar winter cap of continuous darkness An analysis of the MY29 temperature data was performed to generate an annual average surface temperature metric that was then used to both inform the design of and to constrain the computation of the DAET climate model The modelling analysis suggests that the Martian atmosphere is fully transparent to surface emitted thermal radiant energy
Keywords: mars; MY29; atmospheric dynamics; dust opacity; climate modelling